Pulmonary and Systemic Hemodynamics following Multielectrode Radiofrequency Catheter Renal Denervation in Acutely Induced Pulmonary Arterial Hypertension in Swine. (2nd November 2021) - Vakhrushev, Aleksandr D.; Сondori Leonardo, Heber Ivan; Goncharova, Natalia S.; Korobchenko, Lev E.; Mitrofanova, Lubov B.; Andreeva, Elizaveta M.; Koshevaya, Elena G.; Lebedev, Dmitry S.; Mikhaylov, Evgeny N.
Abstract : Objective . We aimed to assess the effects of renal denervation (RDN) on systemic and pulmonary hemodynamics in a swine model of thromboxane A2- (TXA2-) induced pulmonary arterial hypertension (PAH). Methods . The study protocol comprised two PAH inductions with a target mean pulmonary artery pressure (PAP) of 40 mmHg at baseline and following either the RDN or sham procedure. Ten Landrace pigs underwent the first PAH induction; then, nine animals were randomly allocated in 1 : 1 ratio to RDN or sham procedure; the second PAH induction was performed in eight animals (one animal died of pulmonary embolism during the first PAH induction, and one animal died after RDN). In the RDN group, ablation was performed in all available renal arteries, and balloon inflation within artery branches was performed in controls. An autopsy study of the renal arteries was performed. Results . At baseline, the target mean PAP was achieved in all animals with 25.0 [20.1; 25.2] mcg of TXA2. The second PAH induction required the same mean TXA2 dose and infusion time. There was no statistically significant difference in the mean PAP at second PAH induction between the groups (39.0 ± 5.3 vs. 39.75 ± 0.5  mmHg, P > 0.05 ). In the RDN group, the second PAH induction resulted in a numerical but insignificant trend toward a decrease in the mean systemic blood pressure and systemic vascular resistance, when compared with the baseline induction (74 ± 18.7 vs. 90.25 ± 28.1  mmHg and 1995.3 ± 494.3 vs. 2433.7 ± 1176.7   d y n ∗ sec ∗ c m − 5, P > 0.05, respectively). No difference in hemodynamic parameters was noted in the sham group between the first and second PAH induction. Autopsy demonstrated artery damage in both groups, but RDN resulted in more severe lesions. Conclusions . According to our results, RDN does not result in significant acute pulmonary or systemic hemodynamic changes in the TXA2-induced PAH model. The potential chronic effects of RDN on PAH require further research.